Changing Role of Counselors in Schools and Institutions of Higher Education - See, Ching Mey (2006)
Education and training are the most important investment in human capital. Schools and institutions of higher education are challenged to provide conducive and humanize environment of learning which includes caring for the welfare and mental health of our students. Today, schools and institutions of higher education are faced with multitude of complex and multifactored problems, including poverty, gangsterism, violence, drugs, poor academic achievement, and mental health problem such as anxiety and depression. The intensity of students' needs has led many to realize the importance of the counseling programs in comprehensively meeting the needs of all students. Therefore, school and university counselors need to reelok and review their role to guide and counsel students in a changing world and to equip these students with coping skills to become healthy, happy, and productive employees. This paper will discuss the role of school and university counseling, the needs of students, and how counselors work towards meeting these needs.